Prevalence of vulvovaginal candidiasis among pregnant women in Akwa Ibom State, Nigeria - Peace Icha; Maria Bassey; Etanguno Owowo; Idorenyin Jacob; Emem Ntekpere (Microbes and Infectious Diseases)
Background: Vulvovaginal candidiasis is ranked next to bacterial vaginitis as the common and leading vaginal infection affecting greater number of women of childbearing age across the world. Hence, the objective of this study was to investigate the prevalence of vulvovaginal candidiasis among pregnant women in Akwa Ibom State, Nigeria. Methods: High vaginal swab (HVS) samples were collected from 360 pregnant women selected from public health facilities in Akwa Ibom State and tested for the presence of Candida species using standard microbiological methods. Results: The result revealed an overall prevalence of 87(24.16%), significantly (P = 0.05) associated with the socio-demographic characteristics of the pregnant women. Higher prevalence was obtained among pregnant women who were aged 26-30 years 24(27.58%), married 33(37.93%), illiterate 25(22.98%), engaged in businesses 22(25.28%), in their third trimester 42(48.27%), depended on junk nutrition 33(37.93%), had itchy signs/symptoms 39(44.82%), and leaving in urban residence 38(43.67%). The Candida species encountered were C. albicans 68(78.2%), C. tropicalis 12(13.8%), C. krusei 6(6.9%), and C. parapsilosis 1(1.1%). These were 100% susceptible to fluconazole, clotrimidazole, and nystatin, except C. parapsilosis with few resistant strains to fluconazole. Molecular analysis revealed resistance encoded genes CAN1FR, ITS1, and ITS4 in the fluconazole resistant C. parapsilosis. Conclusion: The prevalence rate of VVC among the pregnant women in Akwa Ibom State is relatively high. Routine medical services, proper diagnosis before treatment, and avoidance of antifungal abuse are recommended. Further studies to include larger sample size and the susceptibility profile of the Candida sp. to other commonly used anti-fungal drugs are suggested.